Gadolinium Chloride Augments Tumor-Specific Imaging of Targeted Quantum Dots in vivo - Diagaradjane, Parmeswaran (2010)
Non-specific sequestration of nanoparticles by the reticulo-endothelial system (RES) results in the degradation of image quality of nanoparticle-based imaging. We demonstrate that Gadolinium chloride (GdCl(3)) pretreatment inactivates RES macrophages thereby increasing circulatory time and amplifying tumor-specific signal of conjugated nanoparticles in vivo. The experimental results were validated using compartmental modeling and the rate parameters for the observed kinetics pattern were estimated. This pretreatment strategy could have broad applicability across biomedical applications utilizing theranostic nanoparticles that are sequestered by the RES.